1968
DOI: 10.1017/s0043174500047494
|View full text |Cite
|
Sign up to set email alerts
|

Germination, Growth, and Ecology of Sicklepod

Abstract: Germination, growth, and potential phytotoxicity of sicklepod (Cassia obtusifolia L.) were studied. Seed germination occurred in the temperature range from 18 to 36 C, but rapid seedling growth occurred only between 30 and 36 C. Seed dormancy caused by a waxy coat resulted in only 15% germination in soil over a 12-month period. A 1:15 (g/ml) water extract of sicklepod tops inhibited germination of cotton (Gossypium hirsutum L.) and oat (Avena sativa L.) seed. Incorporation of sicklepod residues in soil reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 6 publications
(2 reference statements)
2
83
0
Order By: Relevance
“…Previous studies also have shown that scarification markedly increased germination of seeds of S. marilandica (Mitchell, 1926) and of S. obtusifolia (Creel et al, 1968;Singh, 1968;Teem et al, 1980). Additionally, scarified seeds of S. marilandica and S. obtusifolia germinated equally well in light and darkness (Table 2).…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies also have shown that scarification markedly increased germination of seeds of S. marilandica (Mitchell, 1926) and of S. obtusifolia (Creel et al, 1968;Singh, 1968;Teem et al, 1980). Additionally, scarified seeds of S. marilandica and S. obtusifolia germinated equally well in light and darkness (Table 2).…”
Section: Discussionmentioning
confidence: 51%
“…The minimum (DV0) and maximum (DV3) threshold temperatures for S. obtusifolia germination were interpreted initially from germination growth experiments detailed in Creel et al. (1968), Teem et al.…”
Section: The Current Distribution Of S Obtusifoliamentioning
confidence: 99%
“…Webster (2001) also identified sicklepod as one of the 10 most 1 Received for publication September 24, 2003, and troublesome weeds of various broadleaf crops in Alabama, Florida, Georgia, Kentucky, Louisiana, North Carolina, South Carolina, Tennessee, and Virginia. Sicklepod has many characteristics that enable it to thrive in a variety of environments. The weediness of sicklepod can be attributed to its potential to produce many seed (Bozsa et al 1989;Bridges and Walker 1985;Creel et al 1968), seed dormancy and survival (Barrapour and Oliver 1998;Creel et al 1968), hard and waxy seed coat (Creel et al 1968;Egley and Chandler 1978), and inconsistent control with herbicides (Isaacs et al 1989). A sicklepod plant can produce between 750 and 1,000 flowers (Senseman and Oliver 1993) and between 8,000 and 14,000 seed (Bozsa et al 1989;Creel et al 1968).…”
Section: Introductionmentioning
confidence: 99%